1983
DOI: 10.1111/j.1365-246x.1983.tb03338.x
|View full text |Cite
|
Sign up to set email alerts
|

The spatial scale of correlation of the day-to-day variability of Sq

Abstract: It is confirmed that even when disturbance variations are taken into account, the spatial scale of day-to-day variability of S4 is local, that is, of the order of one or two thousand kilometres, rather than globally correlated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…The day‐to‐day variabilities of the daily ranges of geomagnetic solar quiet daily variation ( Sq ) and its associated ionospheric parameters in low and middle latitudes have been studied by many authors, including Chapman & Stagg (1929, 1931), Osborne (1966, 1968), Ogbuehi, Onwumechili & Ifedili (1967), Schlapp (1968), Greener & Schlapp (1979), Hibberd (1981, 1985), Butcher & Brown (1981a,b), Schlapp & Mann (1983), Briggs (1984), Mann & Schlapp (1985, 1987, 1988), Brown (1986), Hibberd & Davidson (1988), Schlapp, Mann & Butcher (1988) and Phillips & Briggs (1991). Similarly, the studies of day‐to‐day variabilities of the Sq daily ranges and associated ionospheric parameters in the equatorial zone included those of Forbush & Casaverde (1961), Osborne (1962, 1963, 1964, 1966, 1968), Ogbuehi & Onwumechili (1964), Onwumechili & Ogbuehi (1965, 1967), Onwumechili (1967), Ogbuehi et al .…”
Section: Introductionmentioning
confidence: 99%
“…The day‐to‐day variabilities of the daily ranges of geomagnetic solar quiet daily variation ( Sq ) and its associated ionospheric parameters in low and middle latitudes have been studied by many authors, including Chapman & Stagg (1929, 1931), Osborne (1966, 1968), Ogbuehi, Onwumechili & Ifedili (1967), Schlapp (1968), Greener & Schlapp (1979), Hibberd (1981, 1985), Butcher & Brown (1981a,b), Schlapp & Mann (1983), Briggs (1984), Mann & Schlapp (1985, 1987, 1988), Brown (1986), Hibberd & Davidson (1988), Schlapp, Mann & Butcher (1988) and Phillips & Briggs (1991). Similarly, the studies of day‐to‐day variabilities of the Sq daily ranges and associated ionospheric parameters in the equatorial zone included those of Forbush & Casaverde (1961), Osborne (1962, 1963, 1964, 1966, 1968), Ogbuehi & Onwumechili (1964), Onwumechili & Ogbuehi (1965, 1967), Onwumechili (1967), Ogbuehi et al .…”
Section: Introductionmentioning
confidence: 99%
“…If the foregoing interpretation is correct, the reason for the differing conclusions of Schlapp & Mann (1983) and Hibberd (1981) become clear. In his original investigation Hibberd selected for examination quiet periods in which there was a large day to day variability, since it is easier to study an effect that is large and recognizable rather than one that is small compared with other effects that may be present.…”
Section: Discussion a N D Conclusionmentioning
confidence: 99%
“…In what follows, the daily ranges of AH, and AH, are denoted by RN and R,, respectively. This conclusion has been challenged by Schlapp & Mann (1983). Using data for all days in 1964 and 1965 they found that the correlations between RN and R , were not significantly different for different degrees of quietness.…”
Section: Introductionmentioning
confidence: 99%
“…The day-to-day variability of S, is a well-known phenomenon which has been studied in some detail. Previous work (Schlapp 1968;Greener & Schlapp 1979) has shown that the spatial scale of the correlation of Sq-ranges between different stations is of the order of 2000 km, and is thus regional rather than world-wide. One of the problems in studying the variability of S, is that, even on the quietest days, there may be some residual disturbance.…”
Section: Introductionmentioning
confidence: 98%
“…Hibberd (1981) has proposed a method o f eliminating much disturbance, based on taking the difference in S, range between stations at different latitudes. Using this method, he claimed that on very quiet days, the day-to-day variations in S, range were more globally correlated than on other quiet days, but Schlapp & Mann (1983) have shown that, when a larger body of data is analysed, no such tendency can be found. Butcher & Brown (1981) have studied the variability in the horizontal component of the S, variation, S,(H), and have found that there are many quiet days when the daily variation is perturbed by the presence of minor disturbances such as negative bays.…”
Section: Introductionmentioning
confidence: 99%